GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU PEMILIHAN JAJAN SISWA PADA KANTIN SEHAT SDN SENDANGMULYO 04 KOTA SEMARANG - Laras Ismiati Indrayana; Ratih Indraswari; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2021)
Good nutrition for school-age children is an investment for the nation. To achieve a good nutritional status for these school-age children, good eating behavior is required according to their needs. These behaviors are acquired through education and environmental support. Apart from their house environment, school is also an environment that form children's eating behavior. Students spend their time eating at school, and also complete their needs by consuming snacks. The canteen as a place for snacking for students affects students' daily eating behavior.The canteen of SDN Sendangmulyo 04 is a healthy canteen set up as an example in Semarang City.Therefore, this study aimed to describe the knowledge, attitudes, and behavior of student snack selection in the healthy canteen of SDN Sendangmulyo 04.The research was a quantitative descriptive study through an online questionnaire given to students of SDN Sendangmulyo 04, by determining the research sample using purposive sampling technique. Based on the research, it was found that 98.9% of respondents had good knowledge of snack selection. As many as 95.9% of respondents also had a good attitude in choosing snacks. And it is known that 56.3% of respondents had a fairly good snack selection behavior.